2015
DOI: 10.1051/0004-6361/201525974
|View full text |Cite
|
Sign up to set email alerts
|

Spiral-like star-forming patterns in CALIFA early-type galaxies

Abstract: Based on a combined analysis of SDSS imaging and CALIFA integral field spectroscopy data, we report on the detection of faint (24 < µ r mag/ < 26) star-forming spiral-arm-like features in the periphery of three nearby early-type galaxies (ETGs). These features are of considerable interest because they document the still ongoing inside-out growth of some local ETGs and may add valuable observational insight into the origin and evolution of spiral structure in triaxial stellar systems. A characteristic property … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 68 publications
4
41
0
2
Order By: Relevance
“…Nonetheless, other sources of ionization may populate these regions too. The most frequent ones are: (i) diffuse ionization ubiquitous associated with old-stellar populations (e.g., post-AGBs; Binette et al 1994;Singh et al 2013;Gomes et al 2016) as shown in the central region of the galaxy at the upper-right panel in Figure 2, IC 4566; and (ii) shock ionization, associated with galactic outflows at the resolution of our data (e.g. Bland-Hawthorn et al 2007).…”
Section: Agn Candidatesmentioning
confidence: 65%
“…Nonetheless, other sources of ionization may populate these regions too. The most frequent ones are: (i) diffuse ionization ubiquitous associated with old-stellar populations (e.g., post-AGBs; Binette et al 1994;Singh et al 2013;Gomes et al 2016) as shown in the central region of the galaxy at the upper-right panel in Figure 2, IC 4566; and (ii) shock ionization, associated with galactic outflows at the resolution of our data (e.g. Bland-Hawthorn et al 2007).…”
Section: Agn Candidatesmentioning
confidence: 65%
“…García-Benito et al 2017;López Fernández et al 2018), showing that the quenching, although it becomes a global process, it has a local origin, and in general it gains strength from the center to the outer regions (González Delgado et al 2016;Belfiore et al 2017;López Fernández et al 2018;Sánchez et al 2018). Previous results have already shown the presence of retired/quenched areas in galaxies that are globally star-forming (e.g., Singh et al 2013), and the presence of star-forming areas in globally retired ones (Gomes et al 2016a). On top of that, we know that SFHs in SFGs are not all the same, presenting a decline toward lower values that depends on both the mass and the morphology (e.g.…”
Section: Discussionmentioning
confidence: 85%
“…Previous studies noticed about the nonneglible fraction of early-type galaxies with star formation (e.g. Thomas et al 2010;Gomes et al 2016a;Lacerna et al 2016, and more reference therein). This fraction is composed, among other groups, by (i) classical early-type galaxies that have recently suffered a rejuvenation induced by the capture of gas, and (ii) compact blue galaxies that probably acquired the early-type morphology in recent dissipation gas-rich mergers (see for a discussion, e.g.…”
Section: Morphological Distribution In the Sfr-m * Diagrammentioning
confidence: 99%
“…Although early-type galaxies are frequently associated with the absence of star-forming regions, recent results indicate that a small fraction of them present H ii regions (e.g., Gomes et al 2016a). They could be either remnants of a former disk or the result of a rejuvenation due to the capture of gas-rich galaxies or in falling gas (Gomes et al 2016a). Table 1 H ii regions are located in late-type galaxies, with only ∼7% of the H ii regions hosted by E/S0 galaxies.…”
Section: Hii Regions Along the Hubble Sequencementioning
confidence: 99%